2000
DOI: 10.1029/1999gb001221
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon and stable carbon isotopic evidence for transport and transformation of dissolved organic carbon, dissolved inorganic carbon, and CH4 in a northern Minnesota peatland

Abstract: Abstract. To elucidate the roles of hydrology and vegetation in belowground carbon cycling within peatlands, radiocarbon values were obtained for pore water dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), CH4, and peat from the Glacial Lake Agassiz peatland. The major implication of this work is that the rate of microbial respiration within a peat column is greater than the peat decomposition rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
188
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(213 citation statements)
references
References 69 publications
22
188
3
Order By: Relevance
“…Interestingly, MES also contained other potential fermentation products, i.e., caproate, propionate, butyrate, isopropanol, and valerate, albeit at much lower concentrations than acetate. Such compounds are frequently observed in methanogenic lake sediments or flooded soils (Lovley and Klug, 1982;Phelps and Zeikus 1985;Chin and Conrad, 1995), but were not detected in OMB and OLI. There, acetate and other fermentation products seemed to play a comparatively minor role in the degradation of organic matter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, MES also contained other potential fermentation products, i.e., caproate, propionate, butyrate, isopropanol, and valerate, albeit at much lower concentrations than acetate. Such compounds are frequently observed in methanogenic lake sediments or flooded soils (Lovley and Klug, 1982;Phelps and Zeikus 1985;Chin and Conrad, 1995), but were not detected in OMB and OLI. There, acetate and other fermentation products seemed to play a comparatively minor role in the degradation of organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies indicated that a decreasing pH resulted in decreasing acetate turnover and in the relative dominance of hydrogenotrophic methanogenesis (Kotsyurbenko et al, 2007), and that the type of vegetation, i.e., dominance of Sphagnum P. E. Galand et al: Carbon isotope fractionation in methanogenic peatlands over vascular plants, coincides with the occurrence of acetate accumulation . When acetoclastic methanogenesis operates, it seems to occur preferably in the upper peat layers, whereas the deep layers are dominated by CH 4 production from H 2 /CO 2 (Popp et al, 1999;Chasar et al, 2000;Kotsyurbenko et al, 2004). These observations indicate that the quality of the degradable organic substances may affect the path of CH 4 production .…”
Section: Introductionmentioning
confidence: 99%
“…In general, such organic samples may be of low geochemical abundance, obtained in low yields after processing, require minimally invasive sampling to avoid methodological artifacts, or where increased sub-sampling (e.g., for additional complementary measurements or finer timeresolved analyses) is desired in systems otherwise constrained. Some possible examples include simplified porewater (Bauer et al 1995;Chasar et al 2000;Wassenaar et al 1990) analyses, observing rainwater DOC concentration and isotope ratio (Raymond 2005) evolve during a storm or brief shower, determining groundwater organic carbon fluxes and/or aquifer residence times (Burr et al 2001), monitoring the organic content of fluids within or pumped through organisms (Yahel et al 2003) isotopically, or sub-sampling vent waters to complement a suite of chemical analyses with Δ 14 C and δ 13 C measurements. Successful analyses of diluted seawater suggest that, with further testing, this reactor may also be useful in processing pure freshwater samples.…”
Section: Discussionmentioning
confidence: 99%
“…Dissolved organic carbon (DOC) and total dissolved nitrogen (TDN; as dissolved organic and inorganic N; DON, DIN) broadly influence terrestrial and aquatic ecosystem function and greenhouse gas emissions as they are biogeochemically cycled within soils (van Hees et al 2005, Weintraub andSchimel 2005), transported laterally to aquatic systems, and processed (Aufdenkampe et al 2011) and/or exported to coastal environments (Holmes et al 2011). Mineralization of DOC in soils and surface waters produces CO 2 and CH 4 that are emitted to the atmosphere (Chasar et al 2000, Bengtson and Bengtsson 2007, Drake et al 2015, and DON and DIN are essential nutrients that enhance primary production (Keuper et al 2012(Keuper et al , 2017 and decomposition (Mack et al 2004, Wickland et al 2012. Given the importance of DOC, DON and DIN to terrestrial and aquatic ecosystem function and gaseous and lateral fluxes, it is critical to quantify sources that become newly available as permafrost thaws.…”
Section: Introductionmentioning
confidence: 99%